Historia natural de la colelitiasis: Incidencia de colecistectomía en un área urbana y una rural mapuche, en la última década - Pérez-Ayuso,Rosa María (Sociedad Médica de Santiago, 2002)
Background: Cholelithiasis is the second cause of hospital admissions in Chile. Aim: To study the prevalence of symptomatic gallstone disease and opportunity of cholecystectomy in La Florida, Santiago and among Mapuche Indians in Huapi Island. Patients and methods: In the period 2000-2001, we contacted to 71% (1127 subjects) and to 61% (145 subjects) patients of La Florida and Huapi Island, respectively, that had previously participated in an epidemiological study on cholelithiasis in 1993. We defined symptomatic gallstone patients as those with a history of biliary colic. Each patient was subjected to gallbladder ultrasound. Results: In 1993, 30-35% of gallstone patients were symptomatic (~70% women). During the lapse 1993-2001, only 50% of subjects from La Florida and 25% of patients from Huapi Island were cholecystectomized (p <0.05). Fifty percent of cholecystectomies were emergency operations. In 38 symptomatic Mapuche Indians from Huapi, cholecystectomy was indicated in 2001. After five months of the indication, only one of these subjects had been operated. Laparoscopic cholecystectomy represented 40% of all cholecystectomies performed in the National Health Service Hospitals. Conclusions: This study demonstrates an unacceptable high prevalence of symptomatic gallstone patients remaining non-operated in both the urban and rural communities. This reciprocally correlates with the high frequency of emergency cholecystectomies and the high incidence of gallbladder cancer among Chileans. This study contrasts negatively with the situation of Scotland, where 73.5% of cholecystectomies were laparoscopic in 1998-1999. To reach Scotland standards, the Chilean Public Health System should increase the number of cholecystectomies from 27,000 in 2001 to 57,510 (Rev Méd Chile 2002; 130: 723-30)